Brown algae-functionalized clays as a novel biosupports for lead-free bismuth halide perovskites in the CO2 reduction - Mellado-Lira, Emireth A.; Luévano-Hipólito, Edith; Garay-Rodríguez, Luis F.; Torres-Martínez, Leticia M. (Frontiers in Fuels, 2026)
IntroductionOne of the main environmental problems is air pollution due to high CO2 emissions, a greenhouse gas that contributes to climate change because of the excessive use of fossil fuels. For this reason, CO2 reduction emerges as a promising solution by converting it into renewable fuels using sunlight and advanced semiconductor materials. Recently, hybrid systems based on artificial leaves composed of lead-free halide perovskites and porous support materials have been demonstrated to be highly efficient for CO2 reduction. In addition, the recycling and utilization of natural sources such as the brown algae, considered a plague in the Caribbean, represents an additional advantage for the pollution reduction, carbon sequestration, and social and economic impacts.MethodsThis research proposes an innovative solution to address this environmental problem by demonstrating that hybrid systems based on bismuth halide perovskites (K3Bi2I9) and brown algae-functionalized clay biosupports are promising for the reduction of CO2 with high efficiencies for formic acid production (2.5 mmol h-1) under visible light. The content of the brown algae was investigated to find the best load that promotes higher and stable CO2 reduction efficiencies.ResultsThe presence of the brown algae enhanced light absorption by its chlorophyll, provided free electrons to the semiconductor and highly reactive species (•OH), that favored the formation of C1-C3 products, e.g., HCOOH, CH3COOH, and CH3(CH2)2OH, with efficiencies in the order of >1 mmol. In addition, the stability of the hybrid systems was demonstrated after five hours of continuous visible light irradiation in liquid phase, which analysis of the medium showed a minimal leaching of potassium.DiscussionThe addition of 5 wt.% brown algae in the clays promoted both high efficiency and stability of the hybrid system by preventing cracking, while promoting a porous framework that maintained effective CO2 adsorption. This enhanced effect was attributed to efficient perovskite encapsulation and the presence of chlorophyll (from algae) acting as an electron donor, enhancing light absorption and charge transfer. This synergistic effect enabled efficient CO2 conversions to C1–C3 value-added products. In conclusion, this work demonstrated that the utilization of abundant natural materials such as clays and sargassum supports an ecological and scalable approach while addressing global and local environmental problems.